Analysis of coolant flow distribution characteristics at core inlet of small pressurized water reactor under rolling condition - Zeng, Jinyuan; Mao, Yulong; Li, Bingwen; Zhu, Jianmin; Hu, Yisong; Chen, Jun (Frontiers in Energy Research, 2024)
The flow distribution characteristics at core inlet directly determines the thermal and hydraulic characteristics in the core, and it is closely related to the safety of nuclear reactor. The primary coolant is subjected to additional inertial force in ocean motion, which influence the flow distribution characteristics at core inlet. In the present paper, numerical simulation method is adopted to analyze the coolant flow distribution characteristics at core inlet of the Reactor Pressure Vessel (RPV) of a Small Reactor under rolling condition. Then the results of the flow distribution characteristics were compared with those under steady state. The results show the variation range of flow distribution factors in each channel under rolling condition is within 5%. And the uneven distribution of coolant at the core inlet increases with the increase of rolling amplitude, and decrease with the rolling period in short period. Standard deviation of flow distribution factor at the core inlet changes little under rolling condition, which indicates the flow distribution at the core inlet keeps good uniformity.